Harmsworth popular science - Mee, Arthur (London The educational book company, 1905)
Harmsworth Popular Science was a fortnightly (14 days) series of magazine publications forming an encyclopaedic series of science and technology articles published in the early years of the 20th century, and completed about 1913.It was humanist and modernist in tone, and supported the then-fashionable ideas of eugenics and free market economics. Britain (especially Birmingham) was then considered by the British people to be "the workshop of the world" and the magazine duly celebrated British technical and cultural innovation from Charles Darwin to Guglielmo Marconi.Volume One contained a foreword entitled "The Story of This Book" which outlines the various groups:Group 1: The Universe, "The Making of worlds" which speculates about the place of Earth in CreationGroup 2: The Earth, "The Earth we live on" which starts with 'a molten ball of iron...'Group 3: Life, "Life takes possession" which is Darwinian in toneGroup 4: Plant Life, "The Earth Alive" which has a pre-creationist style "The Hand that made..."Group 5: Animal Life, "The forerunners of Man" describes fossils to speculates about earlier intelligent life formsGroup 6: Man, "Man Appears" speculated about the origin and evolution of human brainsGroup 7: Health, "Man Builds up Strength" covers sanitation, diet and modern medicine such as X-ray and contained biographies on 500 scientists and a bibliography of 1000 scientific books.[citation needed]Group 8: Power, "Man finds Power" covers steam, and 'new' central generation of electricityGroup 9: Industry, "Man Uses Power" Britain as the workshop of the world was its themeGroup 10: Commerce, "Man Buys and Sells" and the dawn of world trade "America sells cotton..."Group 11: Society, "Man organizes society" foresees "The Federation of the World"Group 12: Eugenics "Man Creates The Future" discredited by Nazi Human breeding programs, this section is full of hope that "our children (will pass through) the Gates of Dawn"